a) \(\dfrac{a^{m+1}}{a^{m+2}}\)với \(a=\dfrac{-1}{2}\)
Ta có:
\(\dfrac{a^{m+1}}{a^{m+2}}=\dfrac{a^m.a}{a^m.a^2}=\dfrac{-1}{2}:\left(\dfrac{-1}{2}\right)^2=-2\)
b) \(\dfrac{a^m}{a^{2m+1}}\)với \(a=\dfrac{-1}{4};m=3\)
Ta có:
\(\dfrac{a^m}{a^{2m+1}}=\dfrac{a^3}{a^{2.3}.a}=\dfrac{a^3}{a^6.a}=\dfrac{1}{a^3.a}=\dfrac{1}{\left(-\dfrac{1}{4}\right)^3.\left(-\dfrac{1}{4}\right)}=\dfrac{1}{\left(-\dfrac{1}{4}\right)^4}=256\)
c)\(\dfrac{\left(a+3\right)^3}{\left(a+3\right)^4}\)
Ta có:
\(\dfrac{\left(a+3\right)^3}{\left(a+3\right)^4}=\dfrac{\left(a+3\right)^3}{\left(a+3\right)^3.\left(a+3\right)}=\dfrac{1}{a+3}\)
Chúc bạn học tốt